Effect of exfoliated graphite on electrical properties of chitosan/polyvinyl alcohol films towards toluene - Nazira Binti Nordin (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
In this study, chitosan/polyvinyl alcohol/exfoliated graphite matrix films were prepared to observe the effect of exfoliated graphite concentration on microstructure, electrical conductivity, band gap energy and sensing properties of the films. The chitosan/polyvinyl alcohol/exfoliated graphite film was deposited using various concentration of exfoliated graphite in order to obtain the excellent electric properties. The SEM technique was employed to analyze the structure of the prepared chitosan and the dispersion of exfoliated graphite and polyvinyl alcohol into chitosan matrix. The FTIR was used to analyze the functional groups existence in the chitosan/polyvinyl alcohol/exfoliated graphite films. Next, AFM is employed to study film surface structure in term of surface roughness while UV-Vis spectroscopy method was applied to identify the band gap energy of chitosan and chitosan blended films. Four Point Probe testing was used to determine the electrical conductivity of the film sensors. From the result obtained, this project successfully proved that the addition of exfoliated graphite (0.4%) onto chitosan/polyvinyl alcohol film has improved the electrical properties of the films.